ESPEN guidelines on nutritional support for polymorbid internal medicine patients. Issue 1 (February 2018) - Gomes, Filomena; Schuetz, Philipp; Bounoure, Lisa; Austin, Peter; Ballesteros-Pomar, María; Cederholm, Tommy; Fletcher, Jane; Laviano, Alessandro; Norman, Kristina; Poulia, Kalliopi-Anna; Ravasco, Paula; Schneider, Stephane M.; et al.
Summary: Background & aims: Polymorbidity (also known as multimorbidity) – defined as the co-occurrence of at least two chronic health conditions – is highly prevalent, particularly in the hospitalized population. Nonetheless, clinical guidelines largely address individual diseases and rarely account for polymorbidity. The aim of this project was to develop guidelines on nutritional support for polymorbid patients hospitalized in medical wards. Methods: The methodology used for the development of the current project follows the standard operating procedures for ESPEN guidelines. It started with an initial meeting of the Working Group in January 2015, where twelve key clinical questions were developed that encompassed different aspects of nutritional support: indication, route of feeding, energy and protein requirements, micronutrient requirements, disease-specific nutrients, timing, monitoring and procedure of intervention. Systematic literature searches were conducted in three different databases (Medline, Embase and the Cochrane Library), as well as in secondary sources (e.g. published guidelines), until April 2016. Retrieved abstracts were screened to identify relevant studies that were used to develop recommendations, which were followed by submission to Delphi voting rounds. Results: From a total of 4532 retrieved abstracts, 38 relevant studies were analyzed and used to generate a guideline draft that proposed 22 recommendations and four statements. The results of the first online voting showed a strong consensus (agreement of >90%) in 68% of recommendations and 75% of statements, and consensus (agreement of >75–90%) in 32% of recommendations and 25% of statements. At the final consensus conference, a consensus greater than 89% was reached for all of the recommendations. Conclusions: Despite the methodological difficulties in creating non-disease specific guidelines, the evidence behind several important aspects of nutritional support for polymorbid medical inpatients was reviewed and summarized into practical clinical recommendations. Use of these guidelines offer an evidence-based nutritional approach to the polymorbid medical inpatient and may improve their outcomes.